Pengaruh Shopping Lifestyle, Fashion Involvement terhadap Impulse Buying Behavior Konsumen pada Inong Scarf Banda Aceh - Ersa Kamila; Erlinda Erlinda; Nara Pristiwa (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The development of fashion trends and changes in shopping lifestyles have made consumers more prone to spontaneous purchases, especially for fashion products such as hijabs. Impulse buying behavior is influenced by shopping lifestyles that reflect shopping patterns and interests, as well as fashion involvement that indicates the level of consumer engagement with fashion. This is important to examine in order to understand the factors that influence impulse buying among Inong Scarf consumers in Banda Aceh. This study aims to determine how Shopping Lifestyle and Fashion Involvement influence Impulse Buying Behavior among Inong Scarf consumers, both partially and simultaneously. The method used in this study is quantitative with a sample size of 96 respondents. The research data was collected through questionnaires. Hypothesis testing was conducted using multiple linear regression analysis, t-tests (partial), and f-tests (simultaneous). The aim was to determine the independent variables for the dependent variables. The results of the study show that shopping lifestyle (X1) has a positive and significant effect on impulse buying (Y) with a t-value of 10.330 > t-table 1.985 and sig 0.000 < 0.05, while fashion involvement (X2) is not significant with a t-value of 0.954 < t-table 1.985 and sig 0.343 > 0.05. Simultaneously, the f-value is 171.697 > f-table 3.094 and sig 0.000 < 0.05, meaning that both variables together have a significant effect. The R value of 0.887 indicates a very strong relationship, and R² of 0.782 or 78.2% indicates that impulse buying is explained by these two variables, while 21.8% is influenced by other factors. In conclusion, shopping lifestyle is the dominant factor influencing impulse buying among consumers of Inong Scarf Banda Aceh.